PENGUATAN KOMPETENSI KEAGAMAAN SISWA KELAS X SMK PGRI 2 PONOROGO MELALUI PROGRAM PESANTREN KILAT - NUHA, ULIN; ILMIAH, ULI TARBIATI; MAULIDIN, SYARIF (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2024)
This study aims to analyze the strengthening of religious competence among 10th-grade students at SMK PGRI 2 Ponorogo through the short pesantren (Islamic boarding school) program. This program is designed to enhance students' understanding of Islam, covering topics such as tauhid (faith), akhlak (morality), ibadah (worship), and the Qur'an. The primary focus of this research is to assess the effectiveness of the pesantren kilat program in improving students' religious competence in terms of cognitive, affective, and psychomotor aspects. The research was conducted using a qualitative approach, involving observation, interviews, and documentation. The results indicate that the pesantren kilat program successfully strengthened students' religious competence, with improvements observed in their understanding of proper worship practices, attitudes toward religious teachings, and skills in performing religious rituals. This success is supported by high-quality teaching in line with the curriculum, effective teaching methods, and the support of parents and the pesantren administration. Based on these findings, it is recommended to further develop the pesantren kilat program, focusing on enhancing teaching quality and providing more comprehensive evaluations, as well as expanding its implementation in other schools. ABSTRAKPenelitian ini bertujuan untuk menganalisis penguatan kompetensi keagamaan siswa kelas X SMK PGRI 2 Ponorogo melalui program pesantren kilat. Program ini dirancang untuk meningkatkan pemahaman agama Islam siswa dengan materi yang meliputi tauhid, akhlak, ibadah, dan Al-Qur'an. Fokus utama penelitian ini adalah untuk menilai keberhasilan pelaksanaan pesantren kilat dalam meningkatkan kompetensi keagamaan siswa dari segi aspek kognitif, afektif, dan psikomotorik. Penelitian dilakukan dengan menggunakan pendekatan kualitatif melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa pesantren kilat berhasil memperkuat kompetensi keagamaan siswa, di mana siswa menunjukkan peningkatan pemahaman dalam tata cara ibadah, sikap terhadap ajaran agama, serta keterampilan dalam melaksanakan amalan agama. Keberhasilan ini didukung oleh kualitas pengajaran yang sesuai dengan kurikulum, metode pembelajaran yang efektif, serta dukungan orang tua dan pengurus pesantren. Berdasarkan temuan ini, disarankan untuk mengembangkan program pesantren kilat lebih lanjut, dengan fokus pada peningkatan kualitas pengajaran dan evaluasi yang lebih komprehensif, serta memperluas implementasi program di sekolah-sekolah lain.